That’s Gonna Leave a Mark: Positionality and Secondary Trauma in Researching Mass Killing and Genocide - Nelson, Todd H. (Journal of contemporary ethnography, 2024)
In this article, I describe two fieldwork experiences dealing with traumatic subject matter: a three-month trip to the Russian Federation, researching the crimes of Stalin against the Soviet population, and a two-week odyssey across Poland, researching memorialization of the Holocaust as it occurred there. I had a much more difficult time on the Polish trip. These trips took place at different times, and my positionality had changed dramatically between the two experiences. The other relevant factor in each case was the nature of the material itself and the extent to which I was exposed to it. The Stalinist Terror is much more submerged in Russian society, for example, and it was often challenging to find evidence that it had occurred, as this involved travel to often far-flung Gulag and mass execution sites. In the Polish case, however, the Holocaust narrative and evidence of its occurrence was front and center in my experiences there, to the extent that the ubiquity of sites where terrible events occurred became overwhelming. The interaction of my positionality and the extent to which I was exposed to different types of traumatic experience, led to widely differing emotional tolls on my psyche in each case. I hope an analysis of this interaction, and the differing effects it produced provides information about planning and executing research on traumatic subjects that is valuable to others preparing to undertake it. (Or perhaps it will provide a cautionary tale about what to avoid). This article adds to the literature on personal negative outcomes experienced by those researching traumatic subject matter, particularly in the social sciences.